Cardiac emergency readiness: A community-level assessment of CPR knowledge in Al-Baha - Mohammad I. Barnawi; Hamdah A. Alshmrani; Ruba D. Alghamdi; Sarah I. Alghamdi; Sarah M. Alghamdi; Bushra Alghamdi; Khalid A. Alzahrani (Journal of Family Medicine and Primary Care)
Context: Cardiopulmonary resuscitation (CPR) is a crucial lifesaving technique in cases of cardiac arrest and should be performed by any member of the community. Aims: To investigate the level of knowledge regarding CPR among the general population in the Al-Baha region, Saudi Arabia. Settings and Design: A cross-sectional study was conducted in Al-Baha from July 1, 2023 to August 1, 2023. Methods and Material: Inclusion criteria were individuals aged 18 and above living in Al-Baha who consented to participate. Exclusion criteria included individuals under 18 years old, healthcare professionals, residents outside Al-Baha, individuals who refused to participate, and incomplete questionnaires. Data was collected using an anonymous self-administered validated electronic questionnaire in Arabic distributed through social media. Statistical Analysis Used: The Mann–Whitney U test, the Kruskal–Wallis test, the Shapiro–Wilk test, and the Kolmogorov–Smirnov test. Any result below 0.05 (P < 0.05) was considered significant. Results: A total of 852 were included, with 65.0% of respondents female, the largest age group was 18–30 years old (43.9%). A total of 77.5% had sufficient CPR knowledge, with an average score of 11.2 out of 18. While many knew key CPR practices, gaps in knowledge existed, such as when to start CPR (15.8%). Challenges included determining unresponsiveness (26.8%) and fear of causing harm (73.6%). Social media apps were the primary source of CPR knowledge (53.8%), but 70.0% were unaware of available CPR courses, despite 75.0% expressing interest in enrolling. Conclusions: Population of Al-Baha showed a good level of knowledge, however, gaps remained need to be targeted during education efforts. The preference for social media and interest in CPR courses highlight opportunities for enhancing public preparedness.